Food microbiology in the post-COVID-19 era: insights from bibliometric analysis in bioeconomics - Carlos Alberto Zuniga-Gonzalez (Discover Sustainability)
Abstract Background Before the COVID-19 outbreak, food microbiology was essential in identifying and preventing foodborne pathogens like Salmonella and E. coli. The pandemic underscored the importance of this discipline, highlighting the need for enhanced surveillance and microbiological control in the food chain to avert future public health threats. This research aimed to advance knowledge management in bioeconomy, focusing on eco-intensification and biotechnology applications that directly impact food microbiology during the COVID-19 crisis. Methodology The study conducted a comprehensive literature review grounded in the epistemological principles of bioeconomy, utilizing the Bibliometric Scopus database. This approach explored the development of eco-intensification and biotechnology applications within food safety and nutrition microbiology. Results Findings reveal a significant disconnect between research efforts in bioeconomy and food microbiology, emphasizing the need for enhanced interdisciplinary collaboration to address food security and sustainable production challenges. The study advocates for integrating microbiological insights within bioeconomic frameworks to improve food safety and sustainability. The COVID-19 pandemic also exposed vulnerabilities in the food supply chain, leading to shifts in consumer behavior, including increased online food orders and a greater emphasis on hygiene practices and local products, thus highlighting the necessity for more resilient food systems. Conclusion The study concludes that the pandemic has reshaped food production practices, stressing the integration of food microbiology within bioeconomic frameworks. It identifies a gap in interdisciplinary research and suggests recommendations for decision-makers to strengthen public health agendas and foster resilience through eco-intensification and biotechnology applications.